2010
DOI: 10.1074/jbc.m110.175497
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4 Augments and Restores FcγRs-dependent Phagocytosis in Macrophages

Abstract: Phagocytosis by macrophages is essential for host defense, i.e. preventing invasion of pathogens and foreign materials. (6), and the Rho family proteins (Rho (7) and Rac and Cdc42 (8 -10)) are all required for Fc␥Rs-dependent phagocytosis. LTB 4 is a classical lipid chemoattractant derived from arachidonic acid by the actions of 5-lipoxygenase, 5-lipoxygenase-activating protein (FLAP), and LTA 4 hydrolase. LTB 4 attracts neutrophils and eosinophils by the binding to the LTB 4 -specific G-protein-coupled recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 47 publications
(51 reference statements)
1
32
0
Order By: Relevance
“…Balestrieri et al (67) identified no defect in phagocytosis of the yeast cell wall product zymosan in LTC 4 synthase-deficient peritoneal macrophages. In addition, Okamoto et al (68) have shown that BLT1 Ϫ/Ϫ bone marrow-derived macrophages exhibit lower phagocytic capability of IgG-opsonized zymosan but not of non-opsonized zymosan. Although our work focused on AMs, we did observe a similar dependence on 5-LO products for phagocytosis by peritoneal macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Balestrieri et al (67) identified no defect in phagocytosis of the yeast cell wall product zymosan in LTC 4 synthase-deficient peritoneal macrophages. In addition, Okamoto et al (68) have shown that BLT1 Ϫ/Ϫ bone marrow-derived macrophages exhibit lower phagocytic capability of IgG-opsonized zymosan but not of non-opsonized zymosan. Although our work focused on AMs, we did observe a similar dependence on 5-LO products for phagocytosis by peritoneal macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The binding models of the activator 23a and the inhibitor 23d in the linoleic acid bound as well as the arachidonic acid bound h-5-LOX active site were made based on the recently published crystal structure of h-5-LOX (PDB code 3V99) [50]. The model of h-5-LOX was further refined using the related PDB structures 3V98 and 3V92 to model Ile673 and its carboxylic acid of the C-terminal (missing in 3V99), which coordinates the catalytic iron in the active site.…”
Section: Resultsmentioning
confidence: 99%
“…The potential pharmacological effects of 5-LO inhibitors have been explored in various disease models applied to 5-LO-deficient mice. These animals are strongly resistant to the lethal effects of shock induced by platelet activating factor (PAF) [85], and more susceptible to infections with Klebsiella pneumoniae, in line with the role of leukotrienes, and in particular LTB 4 , in neutrophil recruitment and phagocytosis [11][12][13] as well as in antimicrobial host defense [14,16,86]. Moreover, 5-LO-deficient mice demonstrated the involvement of this pathway in respiratory [87,88] and cardiovascular [45,49,50,89,90] disorders.…”
Section: Inhibition Of 5-lo and Flapmentioning
confidence: 99%
“…In this context, it has been shown that LTB 4 exerts a modulatory effect on innate immune cells, driving and controlling the defense mechanisms of this system against bacteria and viruses. For example, LTB 4 stimulates phagocytes to increase the microbial phagocytosis and killing [11][12][13] and enhances the expression of antimicrobial defense [14][15][16][17]. Moreover, LTB 4 impacts the adaptive immunity and regulates the trafficking of B-and T-cells from the lymphoid compartment into peripheral tissues as well as the T-cell responses during the infections [18][19][20][21][22][23][24].…”
mentioning
confidence: 99%